An assessment method for identifying disassembly modules for sustainable product design - Ong, Benedict Zhi Yong (2017)
In order to achieve greater efficiencies during disassembly and product recovery stages, it is necessary to establish disassembly modules for sustainable product design. This research proposes a methodology for assessing modular potential complexity index (MPCI). The objective of this research is to identify ideal disassembly modules based on the MPCI values. The proposed methodology considers attributes unique to disassembly processes during module assessment, making it representative to the requirements at a product's end-of-life stage. With the knowledge of disassembly module configurations, product recovery is more productive, where product recycling and reuse can be made without complete disassembly at component levels. Component and interface complexities are assessed with various factors from design for disassembly (DFD) principles. Then, the disassembly modularity potential of components is determined from a modified disassembly complexity model. Therefore, this research contributes to enhancing product recovery based on disassembly modules. To demonstrate the effectiveness of the proposed methodology, a case study is performed with electric shavers.